2014
DOI: 10.1039/c4cp02886d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the bulk and surface properties of CdSe: insights from theory

Abstract: CdSe, in the form of quantum dots, is a semiconductor material extensively used for photovoltaic applications. We have performed a comprehensive density functional theory investigation of the geometrical and electronic properties of CdSe bulk crystals (for both the wurtzite and zinc blende phases) as well as their wurtzite (10-10) surface. Several combinations of Gaussian-type orbital basis sets and exchange-correlation functionals have been tested with a periodic formalism. The computational method for furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…In more detail, for the synthesis NPLs were separated by centrifugation and were re-suspended in 10 mL of hexane. We investigated these NPLs in detail, from both an experimental and theoretical points of view in our previous works [17][18][19]. TEM views of the NPL are shown in Figure S7 (Supplementary Material).…”
Section: Nanoplatelets Preparation and Ligand Exchangementioning
confidence: 99%
“…In more detail, for the synthesis NPLs were separated by centrifugation and were re-suspended in 10 mL of hexane. We investigated these NPLs in detail, from both an experimental and theoretical points of view in our previous works [17][18][19]. TEM views of the NPL are shown in Figure S7 (Supplementary Material).…”
Section: Nanoplatelets Preparation and Ligand Exchangementioning
confidence: 99%
“…As mentioned, CdSe can appear in two crystalline forms, i.e., the cubic (sphalerite or zinc-blende, space group F-43m) and the hexagonal (wurtzite, space group P63 mc) structures. 80,81 Figure 1d shows the XRD pattern of CdSe-OCPs, in comparison to that of CdSe-QDs, as representative of the crystalline structure of the CdSe-OCP core. These latter evidence a pure sphalerite phase (ICDD card no.…”
mentioning
confidence: 99%
“…39 Several studies can be found concerning the electronic and structural properties of bulk CdSe. [62][63][64][65] In particular, a previous study by some of us 39 led to the development of a computational procedure, based on the use of global hybrid functionals, that serves as a good description of the structural and electronic features of CdSe bulk structures. The same protocol is applied here with the aim of choosing the best DFT approach.…”
Section: Cdse Bulkmentioning
confidence: 99%
“…The same protocol is applied here with the aim of choosing the best DFT approach. However, while in Szemjonov et al 39 a D2 dispersion correction scheme 66 was adopted in combination with each functional tested, we employed here the D3 40 As mentioned above, to simulate the UV-Vis. spectra of the two CdSe bulk phases considered, the SC-Ewald approach was employed.…”
Section: Cdse Bulkmentioning
confidence: 99%
See 1 more Smart Citation